Developing critical cultural competence : a guide for 21st-century educators - Cooper, Jewell E.; He, Ye, Dr.; Levin, Barbara B. (Thousand Oaks, Calif. : Corwin Press, 2011)
'This book shows you how to provide professional development for teachers that deepens their cultural understanding and includes activities for translating new knowledge into action. Companion website available'-- Provided by publisher.
'This book is designed for professional development staff, teacher educators, lead teachers, administrators, and other school leaders who want to engage teachers in developing their critical cultural competence. Due to the increasingly diverse nature of today's schools, and imperative to increase the achievement of all students, no matter their background, there is great need for 21st century teachers to develop critical cultural competence. This is done best through on-going professional development for both new and experienced teachers because it requires much more than just knowing about the diverse nature of today's students. While culturally competent teachers can reflect on their own practices, and seek knowledge about their students, families and communities, teachers with critical cultural competence have to become more self-analytical in their reflections, innovative in their actions, and collaborative in helping to transform their schools' culture. Therefore, this book offers numerous activities to engage teachers in the exploration of themselves as a cultural beings and innovative ways to learn more about the diversity of today's students from their families and communities. The book is organized around professional development activities that focus on the three inseparable aspects required for developing teachers' critical cultural competency: understanding of self; understanding of students; and understanding of families and communities. The book concludes with recommendations for how to plan and fund professional development for building teachers' critical cultural competence in order to reach the ultimate goal of increasing student achievement'-- Provided by publisher.
'Includes online facilitator toolkit'--T.p.
Machine generated contents note: AcknowledgmentsAbout the AuthorsForewordPreface Why do we need this book? What is Critical Cultural Competence? Who is this book for? How is this book different from other books about diversity and multicultural education? Organization and Special Features of This Book ConclusionIntroduction: What Do We Need to Do to Prepare Teachers for Today's Diverse Classrooms? Why do we need educators with critical cultural competence in today's schools? How can we move professional development ABOUT diversity'beyond knowledge.'? Who are we in this thing called diversity? How do we leverage assets of students, families and communities? Bringing It All Together Summary of Key Points Reflection and Extension1. Common Practices: How Are We Currently Preparing Educators for Diverse Classrooms? Introduction Common Goals for Multicultural Education Foundational Understandings about Diversity Milner's Five Conceptual Repertoires of Diversity Empathy vs. Sympathy Strength-based Approach Materials and Resources Textbooks Historical and Contemporary Videos Online Learning Resources Guest Speakers Other Commonly Used Activities and Approaches Discussions and Reflection Case Studies and Case Discussions Book Clubs Activity 1-1: Book Club Jigsaw Activity Activity 1-2. The Game of Monopoly(TM) Empathy Activities Summary of Key Points Reflection and Extension Online Extensions2. Who I Am: How Can We Understand Ourselves as Cultural Beings? Introduction Exploring Personal Characteristics and Beliefs Activity 2-1: Autobiographies Activity 2-2: Educational Philosophy Activity 2-3: All about Me Activities Activity 2-4: It's All in a Picture and A Snapshot of Me Activities Revealing Beliefs and Identities to Others Activity 2-5: Intercultural Autograph Hunt Activity 2-6: Bio Poems Activity 2-7: The Privilege Walk Summary of Key Points Reflection and Extension Additional Resources Online Extensions Focus for Professional Learning Communities (PLCs)3. Moving from Beliefs and Visions to Action: How Can We Link Our Personal and Professional Identities? Introduction Activity 3-1: Visioning Activity 3-2: Personal Practical Theories (PPTs) Activity 3-3: Action Research Summary of Key Points Reflection and Extension Additional Resources Online Extensions Focus for Professional Learning Communities (PLCs)4. How do We Prepare Educators to Understand and Appreciate Student Diversity? Introduction From Understanding Diversity to Appreciating Diversity Activity 4-1: Diversity Fact Sheets Activity 4-2: Website Reviews Activity 4-3: Interactive Survey Activity 4-4: Description, Interpretation, and Evaluation Summary of Key Points Reflection and Extension Online Extensions Focus for Professional Learning Communities (PLCs)5. From Critical Awareness to Transformative Action: How do We Prepare Educators to Become Cultural Brokers for Student Success? Introduction From Critical Awareness to Transformative Action Cross-cultural Competence and Critical Self-Reflection Activity 5-1: Active Listening Activity 5-2: Classroom Observation Analysis Activity 5-3: ABC's Project Summary of Key Points Reflection and Extension Online Extensions Focus for Professional Learning Communities (PLCs)6. Learning about the Community: How Can We Learn More ABOUT Parents and Families? Introduction Standards-based Reform Benefits of Invoving Parents and Families in Schools Traditional Ways of Involving Parents in Schools Non-traditional Approaches to Parent and Involvement Barriers and Facilitators to Involvement Extending Traditional Approaches to Parent and Family Involvement Activity 6-1: Touring the Neighborhood'The Do's and Don'ts Activity 6-2: Home Visits at the Beginning of the School Year Activity 6-3: Preparing for the First Parent Conference Summary of Key Points Reflection and Extension Online Extensions Focus for Professional Learning Communities (PLCs)7. Community-Based Learning: How Can We Learn FROM Parents, Families, and Communities? Introduction How diverse are families and our communities? Partnering with Parents, Families, and Communities What is community-based learning? Community-Based Learning Activities Activity 7-1: Home-Community Camera Adventure Activity 7-2: Walking a Mile in Another's Shoes Transformative Effects of Community Adventures Summary of Key Points Reflection and Extension Online Extensions Focus for Professional Learning Communities (PLCs)8. Bringing It All Together: How Do We Maximize Teaching and Learning Opportunities? Introduction Connecting Culturally Responsive Pedagogy and Critical Cultural Competence Taking Risks to Develop Critical Cultural Competence Inspiring Critical Reflection and Awareness Transforming Professional Practice Using Rogers' Adoption of Innovation Theory Using the Concerns Based Adoption Model (CBAM) Planning for Professional Development Before We Start Pre/Post Assessment Follow Up Summary of Key Points A Final Word Additional Resources Reflection and Extension Online ExtensionsReferencesIndex.
Includes bibliographical references and index.
Keywords: Multicultural education -- United States; Cultural competence -- United States; Teachers -- Training of -- United States